Model Spasial Data Panel dalam Menganalisis Faktor-Faktor yang Mempengaruhi Kemiskinan di Provinsi Kalimantan Barat: Spatial Data Panel Model in Analyzing Factors Affecting Poverty in Kalimantan Barat Province - Hairil Al-Ham; Neva Satyahadewi; Nur Asih Kurniawati (Badan Pusat Statistik Provinsi Kalimantan Barat, 2024)
Poverty is a complex and multidimensional problem in many countries, including Indonesia, which includes a lack of access to economic resources, education and adequate health services. In 2023, the percentage of the poor people in West Kalimantan Province has decreased to 7.03%, while the target of the RPJMD for West Kalimantan Province is 6.92%. One of the efforts that can be made to overcome this problem is by determining the factors that influence poverty. This research focuses on modeling with a spatial panel econometric approach on the percentage of the poor population. With this modeling, time period effects and spatial effects can be obtained on the percentage of poor people in districts/cities in West Kalimantan Province. The factors analyzed consisted of four sectors, namely education, social, health and employment. The panel data regression model obtained from this study is random effect. Then, in testing spatial effects, the results obtained showed that there was spatial autocorrelation and spatial dependence on error. So the analysis was continued using the spatial error model-random effect (SEM-random effect). The influence between locations or in this case districts/cities is measured using the queen contiguity spatial weighting matrix. From the model formed, it was found that districts/cities that are close to each other have an influence on reducing the percentage of the poor population in West Kalimantan Province. There are two variables that have a significantly influence the percentage of poor people in West Kalimantan Province. The school participation rate has a positive effect, while the percentage of the working population in the labor force has a negative effect on the percentage of the poor.